PENGARUH STRES KERJA DAN KONFLIK INTERNAL TERHADAP PRESTASI KERJA KARYAWAN PT. PERMATA FINANCE DI KABUPATEN BREBES - Lusia Wulandari Sutejo (Jurnal Strategik, 2019)
Abstract This study takes the title "The Effect of Job Stress and Internal Conflict on Employee Job Performance of PT. Permata Finance in Brebes Regency ". Theformulation of the problem in this study is how the influence of work stress andinternal conflict partially on employee work performance at PT. Permata Financein Brebes Regency, how the effect of work stress and internal conflictsimultaneously on employee work performance at PT. Permata Finance in Brebes Regency and which variable is the most dominant influence employee work performance at PT. Permata Finance in Brebes Regency. While the results of the t-test using a 95 percent confidence level (α / 2 = 0.05 / 2 = 0.025) and the degree of freedom Nk (43-2) obtained a table of 2.021 and the results of calculations on the SPSS showed X1 = 1.880 which means that the count < t table. This shows that H0 is accepted or work stress significantly does not affect the work performance of PT. Permata Finance. Whereas at X2 there were 1,000 which meant that t count < t table. This shows that H0 is accepted or internal conflicts significantly do not affect the performance of employees of PT. Permata Finance. The results of the F test carried out using a 95 percent confidence level (α = 0.05) and df = n - k - 1 obtained an F table of 3.23. While the calculation results show 2,001. This shows that F count < Ftable which means that the H0 hypothesis is accepted which means that jointly the work stress-free variable and internal conflict do not affect the employee performance variable PT. Permata Finance